Pengaruh Harga, Promosi, dan Kualitas Pelayanan terhadap Minat Belanja Konsumen di Matahari Departement Store - Muhammad Tammy Ikbal Rumengan; Muhammad Tommy Arby Rumengan; Adnan Suhardis; Khairul Riza (Jurnal Bisnis dan Pemasaran Digital, 2022)
Purpose: The purpose of this study is to find out the effect of price on consumer spending interest at Matahari Department store, totaling 70 respondents. While the determination technique by purvosive sampling. Methodology: The sources of data in this study are primary data and secondary data. Where the primary data from observations and questionnaires. While secondary data can be from data that has been documented. While the analysis technique used is multiple regression analysis. Results: The results of multiple regression analysis are Y = 27,597 + 0,284 + 0,431 + 0,291 + e which shows that price, promotion and division of labor have a positive and significant effect on consumer interest. While the results of the test (t) or partial test indicate that the price (0.089) is smaller than that of alpha 5% (0.05) or tcount = 1.725 > ttable 1.66792, it can be concluded that H1 is accepted which means that there is an effect of X1 price on Y. Promotion variable (0.004) is smaller than alpha 5% (0.05) or tcount = 3.004 > ttable 1.66792, it can be concluded that H2 is accepted which means there is an effect of X2's promotion on Y. As well as service quality variable (0.000) is smaller than alpha 5% (0.05) or tcount = 3.694 > ttable 1.66792, it can be concluded that H3 is accepted which means that there is an effect of the price of X3 on Y. The results of the regression test in this study, it is known that the significance value is 0.000. Where it is required that the significance value of F is less than 5% (0.05) or the value of Fcount = 20.526 > Ftable 2.74, which means that there is an effect of price, promotion and service quality variables (X1, X2, X3) simultaneously (together) on consumer interest in PT Matahari Department Store, Tbk.